(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: The field of translation has undergone a profound metamorphosis with the advent and rapid advancement of artificial intelligence (AI). Once a domain almost exclusively reliant on human linguistic and cultural expertise, translation is now increasingly augmented, and in some cases, redefined by AI technologies. This article explores the multifaceted role of AI in translation, examining its historical development from rule-based systems to sophisticated neural machine translation (NMT), its current impact on efficiency, accuracy, and accessibility, and the emerging challenges and ethical considerations. We also delve into future prospects, including the potential for hyper-personalized translation, real-time multimodal translation, and the evolving partnership between human translators and intelligent machines.